Concentrations of macronutrients, minerals and heavy metals in home-prepared diets for adult dogs and cats - Vivian Pedrinelli (Nature Portfolio, 2019)
Abstract Pet owners often don’t acknowledge the need for home-prepared diet formulation by a trained professional and may use recipes from sources such as the internet. Macronutrient and mineral composition of home-prepared diets were analyzed and compared to NRC and FEDIAF recommendations, and heavy metal concentrations were analyzed and compared to FDA maximum tolerable levels (MTL) for dogs and cats. Recipes of home-prepared diets for adult dogs (n = 75) and cats (n = 25) were evaluated. Analyses of protein, fat, and fiber were performed according to AOAC, and mineral and heavy metal analyses were performed using inductively coupled plasma optical emission spectrometry (ICP-OES). None of the diets supplied recommended levels of all nutrients evaluated, and more than 84.0% of diets presented three or more nutrients below recommendations. Nutrients with most levels below recommendations were calcium and potassium in recipes for dogs and iron and zinc in recipes for cats. As for heavy metals, levels of lead, cobalt, mercury, uranium, and vanadium were above MTLs. Results suggest that home-prepared diets may be a health risk to dogs and cats if not properly formulated. Furthermore, the chronic heavy metal intake must be better elucidated in order to understand the full impact of results.